Corrosion behaviour of Al 2009 reinforced with silicon carbide whiskers. - Shamsul, J. B.; Hazimmah, D.S.; Rahmat, Azmi; Bakir, Luay (Universiti Sains Malaysia, 2009)

(untitled)
Objective of this research project is to study the corrosion behaviour of aluminium 2009 matrix composite reinforced with silicon carbide whiskers.The composite is produced by powder metallurgy process.